Research on Alibaba company’s Digital Human Resource management and Recruitment Information Platform: A systematic case study - Cui, Jun; Wan, Qiang; Wang, Wu; Hu, Shunliang; Gan, Zhongxin; Ning, Zihao (International Journal of Global Economics and Management, 2024)
In the 21st century, As data-based human resource management, AI HRM technologists and digital recruitment have become a major trend in the development of enterprises, the multi-faceted video interview artifact will help enterprises to digitally transform their recruitment and create a revolution in video interview efficiency. Although Human resource management, digital recruitment, and the training of talents have gained a lot of experience and methodology. Moreover, This study also uses the Documentary analysis and TAM theoretical model for analysis. The aspect of digital human resource management includes many factors. Alibaba company starts from the human business and human resource meets the end of the business. Alibaba company defines five key end-to-end digital processes and specifications here: employee onboarding, employee deployment, and employee satisfaction. Performance-based compensation, employee ability training, and employee turnover optimization. To sum up, The research of this paper mainly uses the mixed method of qualitative analysis and quantitative mixed analysis to conduct research and analysis, and uses excel or SPSS 27 software to perform ANOVA analysis on the sample data, and concludes the importance of human resources digitization and recruitment to Ali-baba company. The findings of the study not only not only deepen the research on the development of digital human resource management in enterprises, but also provide valuable reference for the research and development of AI technology and new digital technology for human resource management and recruitment platforms.